My lecturer states that the product

$$\sum_{r=0}^\infty \frac{z^r}{r!} \sum_{s=0}^\infty \frac{z^{-s}}{s!}$$

can be written as (with $n = r-s$)

$$\sum_{n=0}^\infty z^n\sum_{r=n}^\infty \frac{1}{r!(r-n)!} + \sum_{n=-\infty}^{-1} z^n \sum_{r=n}^\infty \frac{1}{r!(r-n)!}$$

but I just don't understand how this has happened. Can someone do the algebra step by step please?

This is my attempt:

Set $n=r-s$ then we have $s = r-n$ and

$$\sum_{r=0}^\infty \frac{z^r}{r!} \sum_{r-n=0}^\infty \frac{z^{-r+n}}{(r-n)!} = \sum_{r=0}^\infty \sum_{n=r}^\infty \frac{z^{n}}{r!(r-n)!}$$

  • 1
    $\begingroup$ This is simply regrouping every contribution $z^{r-s}$ such that $r-s=n$, for each $n$ in $\mathbb Z$. $\endgroup$ – Did May 17 '16 at 8:39
  • $\begingroup$ @Did I have edited the question with my attempt. Why has his outer sum got $n$ and inner sum got $r$? $\endgroup$ – user2850514 May 17 '16 at 8:57
  • 1
    $\begingroup$ Right, so the change of variables in the indices is from $(r,s)$ with $r\geqslant0$, $s\geqslant0$ to $(r,n)$ with $n=r-s$, that is, to $(r,n)$ with $r\geqslant0$, $n\leqslant r$, or, equivalently, to $(r,n)$ with $n$ in $\mathbb Z$, $r\geqslant\max(n,0)$. Thus, the double sum is $$\sum_{n=0}^\infty\sum_{r=n}^\infty \frac{z^n}{r!(r-n)!}+\sum_{n=-\infty}^{-1}\sum_{r=0}^\infty \frac{z^n}{r!(r-n)!}.$$ Note the mistake in the claim in your post. $\endgroup$ – Did May 17 '16 at 10:54

Solution in the form requested:

$$\begin{align} \sum_{r=0}^\infty\frac{z^r}{r!}\sum_{s=0}^\infty\frac{z^{-s}}{s!} &=\sum_{r=0}^\infty\sum_{s=0}^\infty\frac{z^{r-s}}{r!s!}\\ &=\sum_{r=0}^\infty\sum_{n=r-\infty}^r\frac{z^n}{r!(r-n)!} &&\text{putting $n=r-s$}\\ &=\sum_{r=0}^\infty\sum_{n=-\infty}^r\frac{z^n}{r!(r-n)!}\\ &=\sum_{r=0}^\infty\sum_{n=-\infty}^{-1}\frac{z^n}{r!(r-n)!}+\sum_{r=0}^\infty\sum_{n=0}^r\frac{z^n}{r!(r-n)!}&&\text{splitting ranges}\\ &=\sum_{r=0}^\infty\sum_{n=-\infty}^{-1}\frac{z^n}{r!(r-n)!}+\sum_{n=0}^\infty\sum_{r=n}^\infty\frac{z^n}{r!(r-n)!} &&\text{swapping ordering order of summation}\\ &=\sum_{n=-\infty}^{-1}\sum_{r=0}^\infty\frac{z^n}{r!(r-n)!}+\sum_{n=0}^\infty\sum_{r=n}^\infty\frac{z^n}{r!(r-n)!}\\ &=\sum_{n=-\infty}^{-1}z^n\sum_{r=0}^\infty\frac{1}{r!(r-n)!}+\sum_{n=0}^\infty z^n\sum_{r=n}^\infty \frac{1}{r!(r-n)!}\qquad\blacksquare \end{align}$$

Solution posted earlier:

The Cauchy product of two infinte series is given by: $$\sum_{r=0}^\infty f(r) \sum_{s=0}^\infty g(s)= \sum_{k=0}^\infty \sum_{l=0}^k f(l)g(k-l)\\ $$

Hence $$\begin{align} \sum_{r=0}^\infty\overbrace{\frac{z^r}{r!}}^{f(r)}\sum_{s=0}^\infty \overbrace{\frac{z^{-s}}{s!}}^{g(s)}&= \sum_{k=0}^\infty\sum_{l=0}^k \frac{z^l}{l!}\frac{z^{-(k-l)}}{(k-l)!}\\ &=\sum_{k=0}^\infty \frac{z^{-k}}{k!}\sum_{l=0}^kz^{2l}\frac{k!}{l!(k-l)!}\\ &=\sum_{k=0}^\infty \frac{z^{-k}}{k!}\sum_{l=0}^kz^{2l}\binom kl\\ &=\sum_{k=0}^\infty \frac{z^{-k}}{k!}(1+z^2)^k\\ &=\sum_{k=0}^\infty \frac{(z+\frac1z)^k}{k!}\\ &=e^{z+\frac 1z}\qquad\blacksquare \end{align}$$

In this particular case, it would have been more straightforward to evaluate the summations individually and then multiply them i.e. $$\sum_{r=0}^\infty \frac{z^r}{r!}\sum_{s=0}^\infty \frac{z^{-s}}{s!} =\sum_{r=0}^\infty \frac{z^r}{r!}\sum_{s=0}^\infty \frac{(z^{-1})^s}{s!} =e^z \cdot e^{\frac 1z}=e^{z+\frac 1z}$$

  • 1
    $\begingroup$ Hi. You haven't answered my question.. I asked for a specific form. Not the closed form of the series. I started from the function $e^{z+1/z}$ and have been asked to find the general $c_n$ in its Laurent expansion. $\endgroup$ – user2850514 May 17 '16 at 10:06
  • $\begingroup$ Edited to address your specific request. $\endgroup$ – hypergeometric May 18 '16 at 8:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.